The library catalogue and the linked data - Serra, Liliana Giusti [UNESP]; Santarem Segundo, Jose Eduardo (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2017)
The article aims to discuss the possibilities of applying semantic web concepts in the library catalogue, through the application of linked data, favoring the exchange of dynamic information, readable by people and machines. The method adopted is an exploratory research through literature, with a selection of texts that discuss the catalogues, semantic web and linked data. The results focus on RDF, presented as a data model that allows the construction of the structure required for Web data connection, providing flexibility in the choice of descriptive elements that are used with library resources. Initiatives of linked data use were identified in libraries, acknowledging results in their employment. The text concludes with the identification of gains from the use of linked data in library catalogues and the need for the data publication be open and interoperable among institutions, expanding the possibilities of new data connections.
Keywords: Catalogue; Linked data; Semantic web; Metadata; Data structure